2000
DOI: 10.1677/joe.0.1660227
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of underfed pigs with GH throughout the second quarter of pregnancy increases fetal growth

Abstract: Circulating growth hormone (GH) concentrations increase in pregnancy and administration of GH during early-mid pregnancy increases fetal growth in well-fed pigs. To determine whether increased maternal GH could promote fetal growth when feed availability is restricted, fifteen cross-bred primiparous sows (gilts) were fed at approximately 30% of ad libitum intake, from mating onwards and were injected daily i.m. with recombinant porcine GH (pGH) at doses of 0, 13·4 0·3 and 25·6 0·5 µg/kg live weight from day 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
3
23
2
Order By: Relevance
“…Similar conclusions were obtained when pregnant gilts received pST or rpST in the first half of gestation (Kelley et al 1995;Sterle et al 1995;Gatford et al 2000;Rehfeldt et al 2001a). Yet, under crowded uterine conditions obtained by unilateral hysterectomy-ovariectomy, rpST increased uterine weight of gilts (Sterle et al 1996).…”
Section: Repeated Injections Of Grf Increase Somatotropin (St) Concensupporting
confidence: 68%
See 1 more Smart Citation
“…Similar conclusions were obtained when pregnant gilts received pST or rpST in the first half of gestation (Kelley et al 1995;Sterle et al 1995;Gatford et al 2000;Rehfeldt et al 2001a). Yet, under crowded uterine conditions obtained by unilateral hysterectomy-ovariectomy, rpST increased uterine weight of gilts (Sterle et al 1996).…”
Section: Repeated Injections Of Grf Increase Somatotropin (St) Concensupporting
confidence: 68%
“…On the other hand, foetal uptake in the present experiment might have been further increased should other placental components have been affected by GRF. Gatford et al (2000) hypothesized that a ST treatment increases foetal growth by increasing the availability of one or more amino acids that usually limit full growth potential of the foetuses.…”
Section: Repeated Injections Of Grf Increase Somatotropin (St) Concenmentioning
confidence: 99%
“…This corresponds to the period of most rapid placental growth and differentiation in the pig (Knight et al 1977). We and others have shown that daily maternal injections of gilts with porcine GH (pGH) during early-mid pregnancy increases fetal growth (Kelley et al 1995, Gatford et al 2000, numbers of muscle fibers in fetuses or progeny at birth (Rehfeldt et al 1993(Rehfeldt et al , 2001b) and increases growth rates and muscle size of their postnatal progeny (Kelley et al 1995, Gatford et al 2003. Some studies have reported that the greatest responses to pGH are greatest in the smallest piglets within each litter (Sterle et al 1995, Rehfeldt et al 2001a, Rehfeldt & Kuhn 2006, suggesting that the effects of pGH are greatest in the most restricted fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…The pregnant gilt is highly sensitive to the metabolic effects of porcine GH and, when treated for various periods between 25 and 94 days of age, fetal growth is enhanced (13,29,31). GH modulates maternal metabolism and uteroplacental transport capacity, thereby promoting greater nutrient availability to the fetus and, consequently, more rapid growth.…”
Section: Discussionmentioning
confidence: 99%